Parietofrontal motor pathways and their association with motor function after stroke. (2nd May 2015) - Schulz, Robert; Koch, Philipp; Zimerman, Maximo; Wessel, Maximilian; Bönstrup, Marlene; Thomalla, Götz; Cheng, Bastian; Gerloff, Christian; Hummel, Friedhelm C.
Abstract : Interactions between posterior parietal motor areas, ventral premotor cortex and primary motor cortex support skilled hand movements. Using tract-related structure-behaviour analysis, Schulz et al. reveal that the integrity of connections between primary motor cortex and both ventral premotor cortex and the anterior intraparietal sulcus affects residual motor output after stroke. Abstract : Abstract : Corticocortical interactions between the primary motor cortex, the ventral premotor cortex and posterior parietal motor areas, such as the anterior and caudal intraparietal sulcus, are relevant for skilled voluntary hand function. It remains unclear to what extent these brain regions and their interactions also contribute to basic motor functions after stroke. We hypothesized that white matter integrity of the underlying parietofrontal motor pathways between these brain regions might relate to residual motor function after stroke. Twenty-five chronic stroke patients were recruited (aged 64 ± 8.8 years, range 46–75, 17 males, one left-handed) and evaluated 34 months after stroke (range 12–169 months) by means of grip force, pinch force and the Fugl-Meyer assessment of the upper extremity. Based on these measures, motor function was estimated applying a factor analysis with principal component extraction. Using diffusion tensor imaging and probabilistic tractography we reconstructed probable intrahemispheric trajectories between the primary motor cortex, the ventral premotor cortex and the anterior and caudal intraparietal sulcus in each patient. White matter integrity was estimated for each individual tract by means of fractional anisotropy. Generalized linear modelling was used to relate tract-related fractional anisotropy to the motor function. We found that the white matter integrity of the fibre tracts connecting the ventral premotor cortex and the primary motor cortex ( P < 0.001) and the anterior intraparietal sulcus and the ventral premotor cortex ( P < 0.01) positively correlated with motor function. The other tracts investigated did not show a similar structure-behaviour association. Providing first structural connectivity data for parietofrontal connections in chronic stroke patients, the present results indicate that both the ventral premotor cortex and the posterior parietal cortex might play a relevant role in generating basic residual motor output after stroke.